An exploration of the overlap between open source threat intelligence and active internet background radiation - Pearson, Deon Turner (Rhodes University, Faculty of Science, Department of Computer Science, 2020)
Organisations and individuals are facing increasing persistent threats on the Internet from worms, port scanners, and malicious software (malware). These threats are constantly evolving as attack techniques are discovered. To aid in the detection and prevention of such threats, and to stay ahead of the adversaries conducting the attacks, security specialists are utilising Threat Intelligence (TI) data in their defense strategies. TI data can be obtained from a variety of different sources such as private routers, firewall logs, public archives, and public or private network telescopes. However, at the rate and ease at which TI is produced and published, specifically Open Source Threat Intelligence (OSINT), the quality is dropping, resulting in fragmented, context-less and variable data. This research utilised two sets of TI data, a collection of OSINT and active Internet Background Radiation (IBR). The data was collected over a period of 12 months, from 37 publicly available OSINT datasets and five IBR datasets. Through the identification and analysis of common data between the OSINT and IBR datasets, this research was able to gain insight into how effective OSINT is at detecting and potentially reducing ongoing malicious Internet traffic. As part of this research, a minimal framework for the collection, processing/analysis, and distribution of OSINT was developed and tested. The research focused on exploring areas in common between the two datasets, with the intention of creating an enriched, contextualised, and reduced set of malicious source IP addresses that could be published for consumers to use in their own environment. The findings of this research pointed towards a persistent group of IP addresses observed on both datasets, over the period under research. Using these persistent IP addresses, the research was able to identify specific services being targeted. Amongst these persistent IP addresses were significant packets from Mirai like IoT Malware on port 23/tcp and 2323/tcp as well as general scanning activity on port 445/TCP.
Keywords: Computer networks -- Security measures; Computer networks -- Monitoring; Malware (Computer software); TCP/IP (Computer network protocol); Open source intelligence